Regulasi Terhadap Penggolongan Obat di Indonesia Pasca Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Muhammad Mauludhin Rif'an; Lidya Shery Muis (Jayapangus Press, 2026)
A regulatory vacuum emerged in drug classification following the enactment of Law Number 17 of 2023 on Health, primarily due to the government’s failure to issue the implementing Government Regulations mandated under Article 320(8) and Article 321(8). This study aims to analyze the regulatory gap resulting from the absence of these implementing regulations and to assess its implications for legal certainty in drug classification.Using a normative legal research method with statutory and conceptual approaches, this study evaluates the legal validity, hierarchical coherence, and substantive adequacy of existing regulations governing drug classification.The results indicate that the classification framework introduced by Law 17/2023 cannot be applied because no technical Government Regulation has been issued to operationalize the classification standards. In practice, there is a regression to the use of old drug classification categories derived from previous regulations. Furthermore, Minister of Health Regulation No. 28 of 2022 and BPOM Regulation No. 21 of 2020 are no longer legally compatible because they rely on Law No. 36/2009, which has been repealed. Their continued use creates inconsistencies within the regulatory hierarchy and weakens the enforceability of drug classification norms.This study concludes that the misalignment between the new statutory mandate and outdated implementing regulations generates significant uncertainty and undermines the effectiveness of pharmaceutical governance. The study recommends the immediate issuance of a Government Regulation to establish a coherent, authoritative, and technologically adaptive basis for drug classification under the current health law framework.